Adsorption of hexavalent chromium onto alkali‐modified biochar derived from Lepironia articulata: A kinetic, equilibrium, and thermodynamic study. (2nd June 2019) - Asadullah,; Kaewsichan, Lupong; Tohdee, Kanogwan
Abstract: Hydrochar obtained after hydrothermal carbonization (HTC) of Lepironia articulata (LA) was modified into biochar by reacting with a specific amount of KOH in a tubular reactor under slow pyrolysis. The physical and chemical properties of the hydrochar and modified biochar were characterized. The performance of modified biochar (LABC) was investigated through batch sorption experiments. Removal (%) and the maximum adsorption capacity ( q max ) of Cr(VI) onto LABC increased up to 98.9% and 28.75 mg/g relative to 63.44% and 21.90 mg/g in unmodified hydrochar (LAHC) at pH 2.0, 313 K, and 200 mg/L, respectively. The sorption kinetics uptake data were best interpreted with pseudo‐second‐order model, and sorption isotherm was simulated with the Langmuir adsorption model. The thermodynamic parameters confirm the adsorption process to be an endothermic, spontaneous, and increased disorder. The overall results revealed that LABC can be utilized as an environmentally friendly, inexpensive, and effective adsorbent in Cr(VI) removal. Practitioner points: Hydrochar and modified biochar prepared from a tropical biomass ( Lepironia articulata ) were successfully used for the removal of Cr(VI) from aqueous solution. Increased specific surface was obtained by applying chemical modification with alkali treatment, contributing to effectiveness as adsorbent. Dimensionless Kc was estimated from the Langmuir fits and then used to estimate thermodynamics of adsorption. The signs of ∆ H °, ∆ G °, and ∆ S ° indicate that the adsorption of Cr(VI) onto LABC was an endothermic, spontaneous, and increased disorder. Abstract : Effective conversion of alternative biomass into biochar have efficiently improved the removal of hexavalent chromium from aqueous solution.